KONSEPTUALISASI METAFORA WACANA POLITIK: STUDI SEMANTIK KOGNITIF - Hari Kusmanto (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2019)
Utilization of linguistic features of metaphors in political communication leads to diverse interpretations and can lead to conflict. The purpose of this study is to describe the conceptualization of political metaphors in the headline. The data in this study are words, phrases and sentences of political discourse metaphors. The source of data in this study is the title of political news in tribunnews.com January-March edition 2019. The data collection technique in this study uses the documentation, listening and note-taking method. Data analysis in this study uses techniques for direct elements (BUL) and is sharpened by cognitive semantic analysis techniques. The results of this study indicate the use of metaphors in online media politics tribunnews.com covering structural metaphors, orientational metaphors, and ontological metaphors. The tendency of the metaphor used is the metaphor of ontology. This shows that speakers utilize metaphors based on their thoughts and experiences.